Short-term consumer cash loans: looking backwards and forwards - Sanders, Ann (My University, 2015)
The concept of borrowing and lending has been around as long as humans have been living communally and is indeed part of the social fabric of communities (Seabright, 2004). The manifestation for consumer’s need to borrow cash for short periods of time came along somewhat later, but the idea of borrowing and lending is as old as the concept of community. Today’s manifestation of that need is frequently found in the form of short-term cash consumer loans, also known as payday loans.
Sponsored by the Marjorie J. and Richard L.D. Morse Family and Community Public Policy Scholarship
Citation: Sanders, A. (2007). Short-term consumer cash loans: looking backwards and forwards. Unpublished manuscript, Kansas State University, Manhattan, KS.
Keywords: Payday loans; Consumer credit; Reports; Reports